PERBANDINGAN EFEKTIVITAS METHOTREXATE DENGAN PENGGANTI METHOTREXATE PADA PASIEN RHEUMATOID ARTHRITIS ( Studi Pada Pasien Rawat Jalan di RSUD Ulin Banjarmasin) - Arlina Fauziah; Abdul Rahem; Anita Purnamayanti (CALYPTRA, 2018)
Background :The occurrence of Methotrexate drug shortage at Ulin Banjarmasin Regional Hospital caused a change of Rheumatoid Arthriris (RA) therapy in outpatients, which was originally used Methotrexate turned into using Leflunomide (Arava) and later on Azatioprine (Imuran). It was necessary to analyze the efficacy between Methotrexate with Methotrexate replacement therapy. Method : Design of the study was anobservational research with retrospective retrieval data.Data analysis using One Way Anova and paired t test. The efficacy of patient therapy RA analyzed from the Disease Activity Score 28 (DAS28) and efficacy persentage. Result :The results of One Way Anova analysis showed no significant difference between all treatment groups (P> 0.05). From a Post Hoc LSD test it was found that there were significant differences between the initial DAS28Methotrexate with the final DAS28Imuran (P = 0.0034), and between the final DAS28 Arava with the final DAS28 Imuran (P = 0.049). And in the Paired t test there were significant on mean differences between the initial and final DAS28Methotrexate, the initial and final DAS28Arava, and the initial and final DAS28Imuran. Conclusion : There was a difference in the efficacy of Methotrexate with Arava and Imuran with Arava but there was no differences in the efficacy of Methorexate with Imuran in outpatient RA patients in RSUD Ulin Banjarmasin